Molecular differences in the KRAS gene mutation between a primary tumor and related metastatic sites – case report and a literature review - Ewa Anna Kosakowska; Rafal Stec; Radoslaw Charkiewicz; Marta Skoczek; Lech Chyczewski (Folia Histochemica et Cytobiologica, 2010)
In recent years the the set of diagnostic tools in colorectal cancers has been extended by the assessment ofthe KRAS gene status. Currently it is a necessary step in order to qualify patients for the targeted therapy. The results ofthe analysis of several studies revealed a high rate of compliance of the KRAS gene mutational status in primary and metastatictumors. In this paper we present a rare case of incompatibility of the KRAS mutations in the primary tumor located inthe colon and metastatic changes in the liver.